Research on Grading Detection of the Wheat Seeds - Xian-Zhong Han; Ke-Jian Wang; Yingchun Yuan; Chen Chen; Liang Liang (The Scientific World Journal)
Evaluating the merits of the wheat seed is an important significance for wheat breeding. We studied analytic hierarchy process (AHP) for seeds grading by digital image processing techniques in the paper. Firstly, preprocess the collected wheat seed images; extract some parameters, such as area, plumpness, rectangular, and elongation of the seed, and then build the level model. Experiments showed the model is right, and level accuracy rate is more than 95%.